Sensitivity Study of the Influence of Blade Sectional Stiffness Parameters on the Aeroelastic Response of Wind Turbines - Chen, Cheng; Wang, Tongguang; Wang, Long (Frontiers in Energy Research, 2021)
With the development of wind turbines as a result of large-scale and offshore trends, the wind turbine size is becoming increasingly larger. The passive control technique is used to alleviate the increasing loads on the blade for the sake of improving the durability of the wind turbine. The ply design of shells considering the coupling effect of bending and torsion is one of the passive control techniques. The bending torsion coupling stiffness is one of the parameters of the blade section stiffness matrix. In order to fully understand the influence of each blade stiffness parameter on the aeroelastic responses of wind turbines and to consider the influence of structural characteristics on the aeroelastic responses in blade design, the influences and sensitivity of each stiffness parameter in the 6 × 6 stiffness matrix of the blade sections on the aeroelastic responses of the wind turbines are systematically studied under steady wind condition. The aerodynamic forces in the aeroelastic model are calculated by an AeroDyn module based on blade element momentum theory, and the structural dynamic responses of the blade are calculated using generalized Timoshenko beam theory and geometric exact beam theory. The NREL baseline 5 MW wind turbine and blade properties are used in this study, where the diagonal stiffness parameters and non-diagonal stiffness parameters of the matrixes of each blade section are scaled according to certain principles. The results show that the axial stiffness, the flap-wise stiffness, and the torsional stiffness in the diagonal are sensitive to the root loads and tip displacement of the blade. The flap-wise bending torsion coupling stiffness, the flap-wise shear-torsion coupling stiffness, and the edge-wise shear-torsion coupling stiffness in the non-diagonal are also sensitive to the aeroelastic responses. For completeness, the effects of other stiffness parameters on the aeroelastic responses are also analyzed and discussed.